Composite indicator of German regional policy and its use for optimizing subsidies to regional labour markets - Andranik S. Tangian (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2005)
German structural policy is characterized by a composite indicator with three targets:(1) minimization of unemployment, (2) maximization of GDP, and (3) equalization of regional unemployment rates. The composite indicator with given target weights is maximized subject to budget constraints and some administrative restrictions. The optimal combinations of target indices obtained for variable weight ratios are to be considered by a policy maker who thereby makes the final choice among already optimized outcomes, not being burdened with adjusting the target weights. The optimization is performed for econometric predictions-2004 which are derived from regional data for 1994-2002. Comparing with the optimal budget distribution, the efficiency of the actual "manual" budget distribution in 2000-2002 is about 4%, that is, the results actually obtained for 6 Bio. EUR could be obtained for 241 Mio.EUR (= 4% of the actual budget). Such a bad implementation of active labour market policies can be responsible for their low efficiency reported in some empirical studies and misinterpreted as their uselessness. Besides, it is found that the most productive jobs (most contributing to GDP) require least subsidies. Finally, taxes expected from new jobs allow to consider the problem from a managerial viewpoint. In particular, the government can maximize tax returns from investments in labour market policies.
Keywords: C33; H25; J68; R00; R15; 330; European Commission; structural funds; regional policy; active labour market policies; equalizing regional unemployment rates; economic growth